DETEKSI DINI PTM MELALUI PEMERIKSAAN TEKANAN DARAH DAN ASAM URAT - Talarima, Bellytra; Lawalata, Ivy Violan (LPPM Institut Pendidikan Nusantara Global, 2023)
Hypertension is called the silent killer because many people do not realize that they have hypertension, the incidence of gout continues to increase with age. This activity aims to provide education and measurement (screening) for blood pressure and uric acid for all educational and educational staff as well as the community around the campus of the Indonesian Christian University, Maluku, totaling 122 people. The method used is point of care testing (POCT) using a blood pressure measurement device (tensimeter) and uric acid through blood tests. The results obtained were that the majority of respondents had a blood pressure category of pre hypertension and above, namely pre hypertension at 33.6%, grade 1 hypertension at 17.2% and grade 2 hypertension at 6.6%, while for uric acid levels the majority of respondents had the category the maximum is 6 – 7.9 mg/dl and above with details of the percentage of uric acid levels of 6 – 7.9 mg/dl amounting to 35.2%, 8 – 9.9 mg/dl amounting to 15.2% and ≥ 10 mg/dl dl of 9.8%. In conclusion, prevention efforts need to be carried out through implementing a healthy diet, good physical activity and controlling genetic factors